Gender-Balanced Slovak in Contemporary Society - Lujza Urbancová (Gender a Výzkum, 2023)
This paper deals with the current social context in which the gender-balanced functions of the Slovak language are being created. The rules that exist for creating and using gender-based Slovak are at odds with contemporary society. This paper examines the mechanism of language changes including gender-balanced language and makes observations about how they are perceived within the communication community in particular. Language is approached as a construct that is a reflection of society and social processes, while at the same time language influences some of these processes in return. Language changes occur more slowly than social ones, or rather, these changes do not respond operatively to changes within society. An exception to this is the enrichment of vocabulary, but conceptual changes progress much more slowly. The fact that language is used to strengthen certain images of the world also plays a role in the process. Language ideology provides this process with new impulses.